FACTORS INFLUENCING THE COMPETITION AMONG THE PARTICULAR TRANSPORT KINDS (Perner's Contacts, 2010)
The paper deals with the competition in transport. It is especially focused on the competition among the particular transport kinds. It concentrates on some important factors that make differences among the transport kinds and, of course, on criteria influencing customers' choice